2016
DOI: 10.1186/s13071-016-1633-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiles of the salivary proteins SP15 and SP44 from Phlebotomus papatasi

Abstract: BackgroundSand fly saliva has been shown to help parasite establishment and to induce immune responses in vertebrate hosts. In the current study, we investigated the pattern of expression of two Phlebotomus papatasi salivary transcripts in specific physiological and seasonal conditions at a hyperendemic area of zoonotic cutaneous leishmaniasis (ZCL) in Iran.MethodsSand flies were collected during 2012–2013, and grouped according to physiological stages such as unfed, fed, semi-gravid, gravid, parous, nulliparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(39 reference statements)
2
8
0
Order By: Relevance
“…Moreover, aging has been proved as another physiological factor affecting the gene expression profiles; however, it is not considered as significant as genotype or sex determination in insects [40]. Also, similar to what has been observed by other researchers [29], the direct relationship was corroborated between the up-regulation of SP15 transcript and aging.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, aging has been proved as another physiological factor affecting the gene expression profiles; however, it is not considered as significant as genotype or sex determination in insects [40]. Also, similar to what has been observed by other researchers [29], the direct relationship was corroborated between the up-regulation of SP15 transcript and aging.…”
Section: Discussionsupporting
confidence: 75%
“…Physiological status of sand flies was considered to determine SP15 gene expression level. Therefore, due to fresh-fed sand flies indicated a significant up-regulation of SP15 compared to un-fed ones [29], we selected only blood-fed sand flies to investigate the pattern of expression for SP15 transcript in different eco-epidemiologic conditions of Northern Khorasan province. After accomplishing definitive identification of female P. papatasi, salivary glands in addition to their head accessories were dissected using sterile forceps, and then were immediately resuspended in 50 μl of RNA-zole ® RT solution (MRC, OH, USA), homogenized, and stored at -20°C.…”
Section: Rna Extraction From Salivary Gland and Leishmania In Wild-camentioning
confidence: 99%
“…Cutaneous leishmaniasis has been observed in 17 out of 31 provinces of Iran (11)(12)(13). The highest disease incidence has been reported in some provinces, such as Khorasan, Esfahan, Ilam, Fars, Yazd, Bushehr, Khuzestan, whereas western and northwest provinces of the country have been associated with the lowest incidence (14).…”
Section: Introductionmentioning
confidence: 99%
“…Another study which contributes to our knowledge of the differential expression of the salivary genes among different groups within a P. papatasi population has been conducted under natural field conditions in Iran. This study has reported the expression pattern of two P. papatasi salivary transcripts of PpSP15 and PpSP44 to be regulated by sand fly blood feeding, activity season, accessory gland status and leishmanial infection [58,59]. In laboratory examinations, immune responses to sand fly saliva have been detected in mice, hamsters, dogs and humans after multiple exposures to the bites or inoculation of dissected salivary glands from female P. papatasi, Phlebotomus argentipes, P. ariasi, P. sergenti, Lu.…”
Section: Sand Fly Saliva and Induction Of Immune Responses And Protecmentioning
confidence: 99%